Indigenous primary culture protocols for human adult skin fibroblast, pancreatic stellate cells, and peritoneal fibroblasts - Supriya Sharma; Gaurav Pande; Mohit Kumar Rai; Vikas Agarwal (Indian Journal of Rheumatology)
Despite availability of commercially available cell lines, primary cultures of cells remain the best available natural resource for in vitro research work. However, establishing primary cultures is challenging and despite availability of many protocols for primary cell cultures reproducibility is lacking either due to cumbersome protocol, need for special reagents, and requirement of training. Herein, we present our simplistic least manipulative protocols for establishing primary human dermal fibroblasts, human pancreatic stellate cells, and human peritoneal fibroblasts that may be followed by other research laboratories for in vitro studies.